Mixed Marriages in Byzantium in the Thirteenth Century - Nicol, Donald MacGillivray (Studies in church history, 1964)
The Church always demanded that the two partners to a marriage should be not only of the Christian faith but also of the same creed and dogma. Marriage with infidels and Jews was declared illegal; but so also was marriage with heretics and, in Byzantine law, with ‘gentiles,’ or those not within the orbit of the Byzantine Church and Empire. The fourteenth canon of the Council of Chalcedon forbade an Orthodox Christian to contract ‘a marriage with a heretic woman’; the seventy-second canon of the Council in Trullo repeated this prohibition, adding that such a marriage, if contracted, should be dissolved; and in the twelfth century the Byzantine canonist Theodore Balsamon ruled that the female partners in such marriages should be excommunicated. These warnings were solemnly reiterated in the imperial legislation of Byzantium from the time of Justinian onwards.